Die konsep, rituele en proses van Afrika-huwelike - Masango, Maake J. (Verbum et ecclesia, 2006)
In many African tribes, sexual relations are legitimate only within the context of marriage. Moreover, all marriages are preceded by extensive preparations involving, inter alia, education (given by the elders of the community) and various religious rites de passage, e.g. circumcision. Boys and girls undergo separate initiations and several types of marriage (monogamy, polygamy, exogamy) prevail within traditional cultures. In this article, the author discusses elements of the variety of betrothal rites prevalent among African tribes as well as a number of global challenges affecting African marriage customs which have managed to hold their own despite the onslaught of westernisation and (post-) modernity.